Keterampilan Guru dalam Membuka dan Menutup Pelajaran untuk Meningkatkan Kreativitas Anak - Robiatul Adawiyah; Kholidah Nur; Annisa Nur; Ainun Atikah (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
Teachers' skills in opening and closing lessons have an important role in creating an effective and conducive learning atmosphere, especially in supporting the development of children's creativity. Opening the lesson in an interesting way can arouse students' curiosity, motivate them, and prepare their minds to receive the material being taught. Meanwhile, closing lessons creatively provides opportunities for students to reflect on learning, strengthen understanding, and develop innovative new ideas. Teachers can use various strategies in both stages, such as the use of interactive media, exploration-based activities, and reflective approaches. Opening lessons that are relevant and contextual helps create a closer connection between students and the learning material. In addition, creative closure encourages children to think critically, analyze information, and produce creative solutions to various problems. Thus, the skills of opening and closing a lesson serve not only as a technical element in teaching, but also as a way to develop students' overall creative potential. Teachers who are skilled in this aspect are able to create interesting, interactive and meaningful learning experiences, thus supporting the development of children's creativity to face future challenges.